KONSEP MANAGEMENT SUMBER DAYA MANUSIA DAN ISLAMIC VELUE: PERSPEKTIF INTEGRASI INTERKONEKSI - Mella Mardayanti; Alfizi Alfizi (LP2M IAI Nazhatut Thullab Sampang, 2023)
Abstrak: Tujuan dari penulisan.Paper ini adalah kajian terkait dengan kajian management sumber daya manusia dan islamic velue: perspketif integrasi interkoneksi, dalam dimensi keilmuan kita dalam kajian Islam ada dua mazhab keilmuan, yang pertama adalah Islamisasi ilmu ala al-Faruqi dan ilmuisasi Islam ala Kuntowojoyo dan terakhir adalah integrasi interkoneksi ala Amin Adullah, selama ini dalam kajian keilmuan sering kali integrasi hanya soal menempelkan kajian umum ke Islam, jadi ilmu Islam hanya sekedar baju yang di tempelkan dan itu sudah terlabel Islam, padahal sejatinya seharusnya lebih dari itu, integrasi adalah proses di mana menyatu semua velue dengan basis filsafat keilmuan yang ada, teori di ambil titik maksudnya / titik Maqasid dalam kajian Islam, titik maghza dalam kajian al-Quran, kita meyakini bahwa al-Quran sebagai hudan adalah bentuk nyata dari integrasi Islam dan umum, maka tidak ada sebenarnya ilmu di luar Islam dan semua ilmu hadir dan datang dari Islam, paper ini akan melakukan kajian terhadap teori-teori MSDM dan kajian islamic velue dengan dimensi atau perspektif Integrasi interkoneksi. Kata kunci: Islamic Velue, Integrasi Interkoneksi, SDM Abstract The purpose of writing this This paper is a study related to the study of human resource management and Islamic velue: perspketif integration of interconnections, in our scientific dimension in Islamic studies there are two scientific schools, the first is the Islamization of science ala al-Faruqi and the science of Islam ala Kuntowojoyo and the last is the integration of interconnection ala Amin Adullah, so far in scientific studies often integration is only a matter of attaching general studies to Islam, so Islamic science is just a shirt that is attached and it has been labeled Islam, when in fact it should be more than that, integration is the process by which it merges all velue with the existing scientific philosophical base, the theory is taken point of meaning / Maqasid point in Islamic studies, the Maqasid point in Islamic studies, the maghza point in the study of the Quran, we believe that the Quran as a hudan is a real form of Islamic and general integration, then there is no actual science outside of Islam and all knowledge is present and comes from Islam, this paper will conduct a study of MSDM theories and islamic velue studies with dimensions or perspectives Interconnection integration. Key words: Islamic Velue, Integrasi Interkoneksi, and SDM